Bottle and sippy cup use is associated with diet and energy intake in toddlers. Issue 4 (1st May 2014) - Ben‐Avraham, Sivan; Hyden, Christel J.; Fletcher, Jason; Bonuck, Karen A.
Abstract The second year of life incorporates a continued shift from a liquid‐ to solid‐based diet. Little is known about the prevalence and dietary impact of bottle and sippy cup use. This paper describes associations between percent of energy consumed via drinking containers (bottles and sippy cups combined) and dietary outcomes, between 1 and 2 years of age. This observational study recruited n = 299 low‐income, nutrition programme clients from the Bronx, NY, whose 12 month olds consumed ≥ 2 non‐water bottles per day. The main exposure variable was percent of energy intake via drinking containers (PEDC), dichotomized at the median into low‐percent–energy‐from‐drinking‐containers (LOW‐C) and high‐percent–energy‐from‐drinking‐containers (HIGH‐C) groups, assessed quarterly, for 1 year. We report 24‐hour dietary recall nutrient and food serving data by LOW‐C vs. HIGH‐C. We employed linear mixed models to study associations between PEDC and nutrient intake. PEDC decreased from 52% to 33% between 1 and 2 years of age in both groups. The LOW‐C group had higher intake of energy, dietary fibre, iron and sodium, grains, protein‐rich foods and sweets. Conversely, LOW‐C group had lower intake of Vitamin D and calcium vs. the HIGH‐C group. PEDC was inversely associated with total energy intake in a model controlling for baseline age, baseline‐weight‐for‐length and gender (β = −5.8, P = 0.029, 95% confidence interval (−10.96, −0.6). Lower bottle and sippy cup use had significant, albeit mixed association with diet quality in the second year of life, and was associated with higher energy intake. Evidence‐based guidelines are needed to determine the appropriate use of those feeding methods.